Vitamin B12-katalysierte Elektrosynthese: Substrat-B12-Coadsorption an der «Glassy Carbon»-Kathode - Hans-Frieder Beer; Rolf Scheffold (CHIMIA)
Adsorption of the catalyst in presence of substrate at a glassy-carbon electrode was found by means of current-concentration measurements with variable catalyst concentrations during the vitamin B12 catalyzed electrochemical reduction of β-bromoethyl benzoat. No adsorption of the catalyst could be found in absence of substrate. An overlay of adsorption with a reaction of (pseudo) 1. order at the electrode surface was observed during experiments with variable substrate concentrations.